ANALISIS DETERMINAN LAMA TINGGAL WISATAWAN HOMESTAY STUDI KASUS KABUPATEN RAJA AMPAT PROVINSI PAPUA BARAT - Parinusa, Sisilia Maria; Ashar, Khusnul; Kaluge, David (Universitas Merdeka Malang, 2019)
Raja Ampat is one of the regencies located in the West Papua Province that has potential coastal and marine island biodiversity as an prospective asset for tourism development. Since the region was declared by the Government as one of the marine tourism destinations, both foreign and domestic tourists started visiting Raja Ampat. Identifying the determinants of length of stay and investigating how far the participation of local community in the development process of marine tourism sector is very essential in sustainable marine tourism in the future. Due to its function to forecast the length of stay and to analyse the carrying capacity of nature-based tourist destination. The objectives of this research is to examine which factors that influence the length of stay of tourist at the locals homestay. The research location was determined by purposive sampling method while the respondents was determined by accidental sampling method. There were 97 respondents that participated in this research which are consisted of 63 foreign tourists and 34 domestic tourists. Multiple regression analysis with Ordinary Least Square method is used as a data analysing technique. The results showed that the average length of stay of foreign tourists is longer than domestic tourist that is 5 days for international tourist and 3 days for local tourist. Based on the regression analysis, it indicates that tourists age, level of income, and accommodation cost are significantly influenced the length of stay of tourists at the locals homestay.